New record of the stingless bee Tetragonula gressitti from India (Hymenoptera: Apidae: Meliponini) - Rathor, Vikram S.; Rasmussen, Claus; Saini, Malkiat S. (Journal of Melittology, 2013)
Tetragonula gressitti (Sakagami, 1978), currently known from southern Vietnam, is here reported for the first time from dense forests in the state of Arunachal Pradesh, India. This new record is about 2000 km northwest of the type locality of T. gressitti in Vietnam and increases to seven the number of stingless bees known in India. Taxonomic comments on T. gressitti are also provided.